Malaysia-China Relations : An Upward Trajectory? - Rayar, Nawaljeet Singh (2019)
Initial expectations of a tougher line against China under the new Pakatan Harapan (PH) government have been premature. Relations instead are on an upward trajectory as the PH government hopes to benefit from engagement with China. Will this last?